Optimization of Abrasive Wear Characteristics of Polyethylene/Acrylate Copolymer Nanocomposites - S. Chockalingam; G. Gopalarama Subramaniyan; Anand Bisen; S. Kaliappan; S. Sekar; Pravin P. Patil; T. Ch. Anil Kumar; B. Ramesh; S. Venkatesan (Advances in Materials Science and Engineering)
Polymer nanocomposites are being used more widely in a variety of industries. As the compatibilizer, Elvaloy-AC-3427 (EAC) was used in addition to Cloisite 30B (C3B) as the reinforcement of filler in this research. For the production of Polyethylene/Cloisite 30B/Elvaloy AC-3427 nanomaterials, a twin-screw extruder is employed. Cloisite 30B was added to the Polyethylene matrix in the range of 2%, 3%, 4%, and 5%. The mechanical and thermal characteristics of the compounds have been examined. Nanocomposites were tested for their tribological properties utilizing abrasive wear load, C3B, and sliding distance which were all taken into consideration while performing the abrasive wear evaluations. Specific wear rate (SWR), coefficient of friction (COF), and weight loss were the abrasive wear test’s output metrics (SWR). For the purpose of enhancing the abrasive wear characteristics, grey relational analysis and grey fuzzy were used. An ANOVA was carried out to examine the connection between input parameters and output variables. Finally, the Polyethylene/Cloisite 30B/Elvaloy AC-3427 nanocomposites abraded wear samples were evaluated microscopically.